PERANAN SEKTOR AGROINDUSTRI KELAPA SAWIT DALAM MENDUKUNG PEREKONOMIAN DI SUMATERA UTARA - MANAOR SILITONGA (JURNAL ILMIAH KOHESI, 2019)
This study aims to determine the role of oil palm agro-industry sector in supporting the economy of North Sumatra. The basic method used in this research is analytical descriptive method. This is done because of North Sumatra as a producer of palm oil in Indonesia. The data used include secondary data that is the area of ​​oil palm, production, productivity, labor and oil palm contribution to the economy. The results show that oil palm plantations in North Sumatra have a large contribution in the economy of North Sumatra. The development of CPO production has resulted in an increase in CPO exports from 2.7 million tons (2010) to 3.8 million tons in 2015. The export value of North Sumatra for palm oil and its derivatives increased from USD 0.7 billion (2000) to USD 4.7 billion (2014). This shows the palm oil industry is the largest contributor of foreign exchange for the economy of North Sumatra. The share of palm oil exports and their derivatives is increasing from 29 percent in 2000 to 50 in 2014 in total exports of North Sumatra. Oil palm plantations in North Sumatra can also absorb labor, rising from 394 thousand in 2000 to 697 thousand in 2015, as well as oil palm growers from 77,000 in 2000 to 189 thousand in 2015, and have far-reaching impacts in business development Small and Medium Enterprises and Cooperatives in North Sumatra, which increased from 565 units in 2004 to 707 units in 2014.